A meta-analysis of the effects of shockwave and high pressure processing on color and cook loss of fresh meat. (October 2017) - Ha, Minh; Dunshea, Frank R.; Warner, Robyn D.
Abstract: Meta-analysis is a statistical approach for investigating experimental differences across studies. Meta-analyses were performed to examine the effects of hydrodynamic processing (shockwave; n = 12 papers) and high pressure processing (HPP; n = 8 papers) on the color and cook loss of fresh meat. Shockwave did not affect color (L*, a*), whereas cook loss was increased by 0.6% relative to untreated meat. HPP resulted in an increase in lightness (L*) and a decrease in redness (a*), with the effect being greater at higher pressures (> 300 MPa vs < 300 MPa). In addition, HPP applied at moderate pressure (< 300 MPa) reduced cook loss but at high pressure (> 300 MPa) the cook loss was increased (− 1.5% vs 3.0% respectively). The increased cook loss with shockwave and high pressure (> 300 MPa) processing needs to be balanced against benefits in texture if this technology is applied to meat. The reduced cook loss of meat treated at moderate pressures (< 300 MPa) is an advantage which would likely improve sensory traits.